Effectiveness of Trade Policy in Nepal - Kafle, Shiba Devi (Economic Journal of Nepal, 2006)
Realizing the fact that foreign trade is an appropriate means for rapid economic development, Nepal is giving importance to the sustainable development of the external sector adopting trade promotion policies in different times. Despite the implementation of a number of policy and procedural reforms to promote the trade sector, several problems are still in existence. Therefore, policies adopted till now are not sufficient. Given the difficult geographical situation, Nepal’s external sector policy should focus on rapid development in infrastructure, establishment of industries that utilize local resources and fulfill local needs as well as can have production surplus to export, creation of tourism friendly environment and massive promotional activities for tourism, etc. Economic Journal of Nepal Vol.29(1) 2006 pp.13-29